2022
DOI: 10.1111/imj.15742
|View full text |Cite
|
Sign up to set email alerts
|

VEXAS syndrome: lessons learnt from an early Australian case series

Abstract: VEXAS is a newly recognised adult-onset autoinflammatory syndrome resulting from a somatic mutation in the UBA1 gene. Herein, we present three cases of VEXAS syndrome in Sydney, Australia, that capture key clinical features and the refractory nature of the condition. They highlight the importance of multidisciplinary collaboration for early diagnosis and the need for new therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…56.1% of included patients had pulmonary involvement at presentation. The most frequently described manifestation was pulmonary infiltrates (43.1%; n = 116) [ 1 , 8 , 12 34 ], followed by pleural effusion (7.4%; n = 20) [ 8 , 18 , 20 , 22 , 24 , 27 , 28 , 32 , 35 ] and idiopathic interstitial pneumonia (3.3%; n = 9) [ 14 , 18 , 25 , 27 , 28 , 32 , 36 , 37 ]. Other pulmonary manifestations described were NSIP ( n = 1) [ 14 ]; bronchiolitis obliterans ( n = 3) [ 14 ]; pulmonary vasculitis ( n = 6) [ 14 , 24 ]; bronchiectasis ( n = 1) [ 14 ]; alveolar haemorrhage ( n = 1) [ 38 ]; pulmonary embolism ( n = 4) [ 35 , 39 41 ]; bronchial stenosis ( n = 1) [ 42 ]; and alveolitis ( n = 1) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…56.1% of included patients had pulmonary involvement at presentation. The most frequently described manifestation was pulmonary infiltrates (43.1%; n = 116) [ 1 , 8 , 12 34 ], followed by pleural effusion (7.4%; n = 20) [ 8 , 18 , 20 , 22 , 24 , 27 , 28 , 32 , 35 ] and idiopathic interstitial pneumonia (3.3%; n = 9) [ 14 , 18 , 25 , 27 , 28 , 32 , 36 , 37 ]. Other pulmonary manifestations described were NSIP ( n = 1) [ 14 ]; bronchiolitis obliterans ( n = 3) [ 14 ]; pulmonary vasculitis ( n = 6) [ 14 , 24 ]; bronchiectasis ( n = 1) [ 14 ]; alveolar haemorrhage ( n = 1) [ 38 ]; pulmonary embolism ( n = 4) [ 35 , 39 41 ]; bronchial stenosis ( n = 1) [ 42 ]; and alveolitis ( n = 1) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study on three patients suggested that tocilizumab associated to low-dosage glucocorticoids may be an effective option in patients without severe hematologic abnormalities. In other cases, the combination of tocilizumab and methotrexate has further improved the therapeutic role of IL-6 inhibition [ 38 ]. Nevertheless, unresponsive patients have also been reported [ 26 , 39 ] and adverse events may be frequent in VEXAS syndrome.…”
Section: Therapy Evidencementioning
confidence: 99%
“…Nevertheless, unresponsive patients have also been reported [ 26 , 39 ] and adverse events may be frequent in VEXAS syndrome. In particular, tocilizumab treatment has been found associated to neutropenia, viral infections reactivations (especially herpes zoster virus), and severe gastrointestinal side effects in VEXAS patients [ 38 , 40 ]. Regarding patients with gastrointestinal involvement, tocilizumab treatment seems to be a risk factor for perforation of the jejunum or ileum in the site of diverticulitis.…”
Section: Therapy Evidencementioning
confidence: 99%
“…As of May 2022, fewer than 300 cases have been reported in the literature (Table ). [6][7][8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Symptoms in the majority of patients begin around age 55 to 65 years, but onset can range from 40 to 85 years. 6,10,13,14 Geographic and ethnic distributions of VEXAS have not been fully defined.…”
Section: Epidemiologymentioning
confidence: 99%